The Resilience of the Sharia Economic System in Facing Various Crises in Post-Pandemic Indonesia - Abi Waqqosh; Emilia Embun Sari; Faisar Ananda; Fitri Nada Zahira; Siti Nurhalimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Sharia economics is considered to be a fairer and more stable economic system than conventional economics. This study aims to analyze the resilience of the Islamic economy in the face of the crisis, which proved to be better in 2008. Many Islamic banks have stronger resilience than conventional banks that use a lot of speculative instruments. Although there is a lot of research on Sharia economic resilience during the pandemic, there is still a lack of studies on post-pandemic resilience. The post-pandemic situation is very important because it builds the economy after a difficult crisis, including in Indonesia, where there is a slowdown in economic growth. The Indonesian government has taken many steps, including monetary policies for economic recovery, such as the PEN Program, which provides tax incentives, the recovery of SOEs, and support for MSMEs. This study has two hypotheses: whether or not the sharia economy is strong in the face of post-pandemic economic instability. The method used is qualitative with expert exploration and comparative analysis. The results show that the sharia economy has advantages such as a fair profit-sharing system, but also faces challenges such as a lack of capital and innovation. Therefore, strengthening regulations and public education is very important for the development of the sharia economy in the future.